Substance P Saliva Reduction Predicts Pharyngeal Dysphagia in Parkinson's Disease - Schröder, Jens Burchard; Marian, Thomas; Claus, Inga; Muhle, Paul; Pawlowski, Matthias; Wiendl, Heinz; Suntrup-Krueger, Sonja; Meuth, Sven G.; Dziewas, Rainer; Ruck, Tobias; Warnecke, Tobias (Frontiers in Neurology, 2019)
Introduction: Although patients with Parkinson's disease (PD) often suffer from oropharyngeal dysphagia, knowledge about the underlying pathophysiological mechanisms is limited. Substance P (SP) is a localization-independent neurotransmitter of the entire nervous system. Reduced levels of SP were found in saliva of patients with impaired cough reflex and in advanced stages of PD. The aim of the study was to investigate SP in PD patients in order to gain further insights into the underlying pathophysiology of PD-related dysphagia and to evaluate the potential of SP as a biomarker for early dysphagia. Methods: Flexible endoscopic evaluation of swallowing (FEES) was used to objectively assess pharyngeal swallowing function. From a cohort of 105 consecutive PD patients twenty subjects were recruited: In ten of them pharyngeal dysphagia was excluded by FEES, the other ten subjects showed signs of early pharyngeal dysphagia defined as hypopharyngeal sensory deficit with mild to moderate vallecular residues after swallowing solid consistencies. Analysis of the Substance P level in saliva of the twenty included PD patients was performed in the clinical on state condition by ELISA-type immunoassay. Significant differences were calculated by using the Mann-Whitney test. Results: Twenty PD patients with a mean age of 69.5 ± 12.5 years (8 female) were included in the study. No significant differences were found regarding gender, age, UPDRS III, Hoehn and Yahr stage, disease duration and Levodopa equivalent dose between the non-dysphagic and dysphagic subjects. Dysphagia was mainly characterized by unrecognized residues in the valleculae without any aspiration risk for all of the tested consistencies in FEES and was thereby scored as mild in all cases. Saliva SP concentrations were significantly lower in PD patients with pharyngeal dysphagia compared to those with a normal pharyngeal swallowing function (9644 pg/mL vs. 17591 pg/mL; p= 0.001). Conclusion: Reduced saliva SP concentrations may predict early pharyngeal swallowing dysfunction in PD patients. This finding supports the hypothesis that an impaired SP mediated neurotransmission has a significant impact for the development of dysphagia in PD patients. Larger studies are needed to confirm SP as a clinical useful biomarker for early detection of PD-related dysphagia.